Metallic bionanocatalysts: potential applications as green catalysts and energy materials. Issue 5 (22nd August 2017) - Macaskie, Lynne E.; Mikheenko, Iryna P.; Omajai, Jacob B.; Stephen, Alan J.; Wood, Joseph
Summary: Microbially generated or supported nanocatalysts have potential applications in green chemistry and environmental application. However, precious (and base) metals biorefined from wastes may be useful for making cheap, low‐grade catalysts for clean energy production. The concept of bionanomaterials for energy applications is reviewed with respect to potential fuel cell applications, bio‐catalytic upgrading of oils and manufacturing 'drop‐in fuel' precursors. Cheap, effective biomaterials would facilitate progress towards dual development goals of sustainable consumption and production patterns and help to ensure access to affordable, reliable, sustainable and modern energy. Abstract : Bacteria can make metallic nanocatalysts, often from waste metal sources. Such bionanocatalysts can have applications in several areas of sustainable energy such as fuel cells, oil upgrading and production of 'drop in' fuels.